BIAYA LINGKUNGAN DAN ENVIRONMENTAL DISCLOSURE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN DI INDONESIA - Nafaliana, Nia; Susanti (Jurnal Bisnis Darmajaya, 2026)
The financial performance of mining companies is influenced not only by economic conditions but also by how they manage and disclose environmental aspects of their operations. Given the sector’s significant environmental impacts, firms frequently allocate environmental expenditures and expand environmental disclosure as a form of accountability to stakeholders. This study examines the effects of environmental costs and environmental disclosure on the financial performance of mining companies in Indonesia. A quantitative approach was employed using secondary data drawn from annual reports and sustainability reports of mining firms listed on the Indonesia Stock Exchange for the 2022–2024 period. Data were analyzed using panel regression with a Random Effects model. The results indicate that environmental costs do not have a significant effect on financial performance, whereas environmental disclosure has a significant negative effect. These findings suggest that broader environmental disclosure increases short-term burdens on companies, which may reduce profitability. Nonetheless, environmental disclosure remains necessary to maintain corporate legitimacy and to enhance stakeholder trust. Therefore, this study underscores the importance of optimal environmental management so that sustainability objectives can be met without compromising financial performance.   Keywords — Environmental Cost, Environmental Disclosure, Financial Performance, Mining.